Influence of Avatar Facial Appearance on Users’ Perceived Embodiment and Presence in Immersive Virtual Reality - Suk, Haejung; Laine, Teemu H. (Electronics (Switzerland), 2023)
Immersive virtual reality (VR) based on head-mounted displays has been identified as one of the key interaction technologies of the future metaverse, which comprises diverse interconnected virtual worlds and users who traverse between those worlds and interact with each other. Interaction in immersive VR entails the use of avatars that represent users. Previous research has shown that avatar appearance (e.g., body type, body visibility, and realism) affects the senses of embodiment and presence, which are among the key indicators of successful immersive VR. However, research on how the similarity between an avatar’s face and the user’s face affects embodiment and presence is lacking. We conducted a mixed-method experiment with 23 young adults (10 males, 13 females, mean age: 25.22) involving a VR scene with rich embodiment, a virtual mirror, and interaction with a virtual character. The participants were assigned to two groups: Group 1 had avatars based on their own faces, and Group 2 had avatars based on a stranger’s face. The results indicated that Group 1 experienced higher embodiment with no significant differences in presence scores. Additionally, we identified moderate and significant correlations between presence and embodiment, including their subscales. We conclude that the realism and similarity in an avatar’s appearance is important for embodiment, and that both embodiment and presence are intertwined factors contributing to immersive VR user experience.
Keywords: avatar; embodiment; facial appearance; immersion; presence; realism; virtual reality